Harnessing labour confrontation : shaping the postwar settlement in Canada - McInnis, Peter S. (Peter Stuart), 1958- (University of Toronto Press, 2002)
"The 1940s, a decade of heightened militancy and struggle on the shop floor and on the picket line, were crucial years in the labour history of Canada. The experience of the Depression, closely followed by the mass mobilization of the workforce during the Second World War and later by the economic optimism of the postwar years, provided the impetus that led to a restructuring of the relationship between labour and the state. In Harnessing Labour Confrontation, Peter S. McInnis examines the reformation of Canadian society and its industrial-relations regime from the perspective of labour organizations and their supporters and from that of government and business. What results is a synthesis of labour and political history in which the author analyses the role of debate and confrontation in the formation of the national postwar compromise and in the birth of the modern welfare state." "McInnis explores the constraints and possibilities that faced the labour movement in that era, as well as the conditions that give rise to industrial legality. He identifies the factors affecting the postwar compromise, including the divided jurisdiction between federal and provincial governments, the return to gender-biased social norms, a developing Cold War climate of national insecurity, and a promise of strong consumer purchasing power based on postwar wage and benefit packages. A formative moment in Canadian history, the 1940s left as a legacy not only the welfare state but also the legal framework that has defined organized labour for five decades."--Jacket